Ciprofloxacin safety in paediatrics: a systematic review - Adefurin, Abiodun; Sammons, Helen; Jacqz-Aigrain, Evelyne; Choonara, Imti (BMJ, 2011)
Objective: To determine the safety of ciprofloxacin in paediatric patients in relation to arthropathy, any other adverse events (AEs) and drug interactions. Methods: A systematic search of MEDLINE, EMBASE, CINAHL, CENTRAL and bibliographies of relevant articles was carried out for all published articles, regardless of design, that involved the use of ciprofloxacin in any paediatric age group ≤17 years. Only articles that reported on safety were included. Results: 105 articles met the inclusion criteria and involved 16 184 paediatric patients. There were 1065 reported AEs (risk 7%, 95% CI 3.2% to 14.0%). The most frequent AEs were musculoskeletal AEs, abnormal liver function tests, nausea, changes in white blood cell counts and vomiting. There were six drug interactions (with aminophylline (4) and methotrexate (2)). The only drug related death occurred in a neonate who had an anaphylactic reaction. 258 musculoskeletal events occurred in 232 paediatric patients (risk 1.6%, 95% CI 0.9% to 2.6%). Arthralgia accounted for 50% of these. The age of occurrence of arthropathy ranged from 7 months to 17 years (median 10 years). All cases of arthropathy resolved or improved with management. One prospective controlled study estimated the risk of arthropathy as 9.3 (OR 95% CI 1.2 to 195). Pooled safety data of controlled trials in this review estimated the risk of arthropathy as 1.57 (OR 95% CI 1.26 to 1.97). Conclusion: Musculoskeletal AEs occur due to ciprofloxacin use. However, these musculoskeletal events are reversible with management. It is recommended that further prospective controlled studies should be carried out to evaluate the safety of ciprofloxacin, with particular focus on the risk of arthropathy.